Debris Crumb - Elhomran, Al-Rahman Abd (Palestinian Territories, 2009)
The film follows the life of children living in the debris left behind by war in Gaza, Palestine Territories. They reflect on their daily struggles, grief and challenges of living in such conditions.
Verzio Film Festival Submission
Keywords: Documentary films